Ambiental Engagement as a Fashion Branding Tool (ModaPalavra e-periódico, 2019)
The present paperis a result of the observation work over Osklen’s brand strategy for the launch campaign of its collaction ‘ASAP –As Sustainable As Possible’ during the winter season of 2018. For this purpose, a qualitative analysis of brand communication was developed,as well as interior layout of stores, choices and decision of the style team on composing this collection and the brand speech which was stablished because of this launch: starting on the brand’s creative diretor voice and going trough communication pieces and advertising campaign.After all the bibliographic study, via exploratory method, it was possible to identify the construction of this discourse based on “ambiental responsibility” cause as a branding tool.
Keywords: fashion; branding; ambiental responsibility